MySpace unraveled : a parent's guide to teen social networking from the directors of BlogSafety.com - Magid, Lawrence J (Peachpit Press, 2007)
To help you understand MySpace, the authors step you through how to set up and personalize a MySpace account and how to manage an online social life. Then they look at how young people are changing the Internet and how to guide them as they navigate the social Web
Age Group: Adult
Includes index.
Keywords: Blogs; Internet -- Safety measures; Internet and teenagers; MySpace (Firm); Parenting